Adverse Prognostic Value of Persistent Office Blood Pressure Elevation in White Coat Hypertension. Issue 2 (August 2015) - Mancia, Giuseppe; Facchetti, Rita; Grassi, Guido; Bombelli, Michele
<x xml:space="preserve">Abstract</x> Stratification of cardiovascular risk is of fundamental importance in white coat hypertension (WCH) to identify individuals in need of closer follow-up and perhaps antihypertensive drug treatment. In subjects representative of the general population of Monza (Italy), the risk of cardiovascular and all-cause mortality was assessed >16 years in stable and unstable WCH individuals, that is, those in whom ambulatory blood pressure (BP) normality was associated with a persistent or nonpersistent office BP elevation at 2 consecutive visits, respectively. Data were compared with those from an entirely normotensive group, that is, ambulatory and persistent office BP normality. Compared with the normotensive group, the risk of cardiovascular and all-cause death was not significantly different in unstable WCH, whereas in stable WCH the risk was increased also when data were adjusted for baseline confounders, including ambulatory BP (hazard ratio, 16; P=0.001 for cardiovascular death and 1.92; P=0.02 for all-cause death). At a multivariable analysis, office BP was among the factors independently predicting death, and results were superimposable with use of Monza population–derived and guidelines-derived cutoff values for ambulatory BP normality (125/79 and 130/80 mm Hg, respectively). Thus, only when office BP is persistently elevated does WCH reflect the existence of an abnormal long-term mortality risk. This means that in WCH office BP is prognostically relevant and that repeated collection of its values is clinically important to better define patient risk.